MICROALBUMINURIA: ASSOCIATION WITH ISCHAEMIC HEART DISEASE IN NON-DIABETICS - Hashim, Rizwan; Nisar, Shazia; Rehman, Khalil ur; Naqi, Naeem (Journal of Ayub Medical College Abbottabad, 2006)
Background: In view of the high morbidity and mortality associated with ischemic heart disease (IHD), the estimation of individual cardiovascular risk over and above the assessment of classic risk factors, such as age, hypercholesterolemia and hypertension, is an important prerequisite for focusing preventive measures and therapeutic measures. Microalbuminuria (MA) as a marker of IHD in nondiabetics is currently under international debate. The present descriptive study undertaken at Combined Military Hospital, Lahore was aimed to determine the frequency of MA in nondiabetic IHD patients. Methods: One hundred consecutive non diabetic patients with IHD (73 males, 27 females). Patients showing clinical albumiuria and with other causes of proteinuria were excluded. Urinary albumin in first morning sample was estimated by immunoturbidimetry method. Albumin to creatinine ratio (ACR) was calculated as mg/g. Results: The frequency of MA ( ACR > 30 mg/g) was 37% in patients. Frequency was highest in older age bracket for both genders. The mean ACR was 131.8±66.2 mg/g. Significant difference was observed in mean MA level among different age groups. Conclusion: MA is common in nondiabetics patients with IHD. The mean level of MA was higher in older patients. Key Words: Ischemic heart disease, nondiabetics, microalbuminuria, cardiovascular risk.